Manajemen Perencanaan Pembelajaran pada Dayah di Aceh - Muhammad Faisal (2022)
Dayah (Pesantren) is the forerunner of genuine education in the archipelago, which only received juridical recognition in 2003 through the National Education System Law No. 20 of 2003. The focus of this study is learning in the dayah education system in Aceh. This research is research with a qualitative approach that produces findings that cannot be achieved by using statistical procedures or by other means of quantification. The location of this research was taken at Dayah Darul Ihsan, Siem, Darussalam, Aceh Besar. Data collection techniques were carried out by observation, interviews, and documentation studies. The collected data is analyzed inductively every time during the research by processing empirical materials. The results of the study indicate that the implications of planning in learning management in Dayah in Aceh are proven by conducting teaching planning because teaching planning is very important to be arranged as optimally as possible before the implementation of the learning process. The implementation implication is done by a) managing the learning process, b) managing the class, c) using media, d) mastery of the educational foundation and e) managing learning interactions. While control is done by evaluating to see where there are weaknesses and what programs have been put in place.